The Determinants of Employee Retention in The Iraqi Banking ‎Sector - Neamah Hussein , Waal; M Hussin, Baharuddin (International Journal of Accounting and Economics Studies, 2025)
Employee retention plays a vital role in organisational success, beginning with an understanding of why individuals choose to join and ‎remain with an organisation. The growing challenge of high turnover rates worldwide makes it increasingly difficult for managers to retain skilled employees. Grounded in social exchange theory, this study assumes that when employees feel valued through organisational ‎practices, they are more likely to respond with commitment, positive attitudes, and supportive behaviours, which strengthen retention. ‎However, there remains a lack of knowledge on how specific organisational factors influence retention in developing contexts, particularly ‎in Iraq. This research investigates the role of supervisor support, working conditions, compensation, work-life balance, career advance-‎ment, and job security in shaping employee retention within the Iraqi banking sector. A quantitative design was employed, with survey data ‎collected from 385 employees across banks in Baghdad, Basra, and Mosul. Structural Equation Modelling (SEM) was used for analysis. ‎Findings indicate that all these factors have a significant and positive effect on employee retention. The study contributes theoretically by ‎integrating social exchange and identity perspectives, and it provides practical implications for policymakers and practitioners seeking to ‎strengthen retention strategies in Iraq’s banking sector and other emerging markets‎.